ANALISIS POTENSI PAJAK REKLAME TERHADAP PENDAPATAN ASLI DAERAH DI KOTA MAKASSAR - Muhaimin Muhaimin; Faidul Adzim; Firmansyah Firmansyah (Jurnal Riset Perpajakan: Amnesty, 2019)
Research aims to know the large number of potential tax billboards in the city of Makassar, billboards tax collection, contributions to the contribution of local income tax, the effectiveness of the poll, as well as increased contribution efforts Income tax on the original revenue of Makassar city. This research uses data collection techniques in the form of literature review, interviews, and documentation. The results showed that the potential of the billboards owned by the city of Makassar for the year 2014 to 2016 increase annually, but there is still a potential that has not been shaken optimally. The Billboards tax collection system in place of the government of DISPENDA Makassar is the official assessment. For the year 2012-2014 the contribution of billboards tax on local tax and local revenue was increased annually, but there was a decline in local tax and local revenue in 2015 and 2016. The Collector